Revealing Gender Ideology in Integrated Korean Language Textbooks through Theme-Rheme Structures: - Triarisanti, Risa; Gunawan, Wawan; Ansas, Velayeti Nurfitriana; Azizah, Asma; Megasari, Jayanti (Anaphora : Journal of Language, Literary, and Cultural Studies, 2025)
This study adopts a Systemic Functional Linguistic (SFL) approach grounded in Halliday’s theoretical framework to investigate Theme-Rheme structures in the Integrated Korean Language textbooks . This research is significant as prior studies on Korean language textbooks have largely overlooked the interplay between thematic structure and ideological representation, leaving a gap in understanding how discourse patterns contribute to implicit cultural messaging. The primary objective is to examine the deployment of marked and unmarked themes as well as the patterns of thematic progression within narrative and descriptive texts. The data are drawn from Volumes 3 and 4 of the textbooks, which encompass cultural, object-related, and activity-based themes. The findings indicate that the majority of clauses adhere to the Simple Linear Thematic Progression pattern, wherein the rheme of one clause becomes the theme of the subsequent clause, thereby contributing to a cohesive and logically sequenced discourse. In certain instances, Complex Linear Progression patterns were also observed, offering extended elaboration of central ideas. Material and relational processes are predominantly employed to represent actions and identity relationships, illustrating how lexical choices such as verbs and conjunctions function to structure the narrative. Furthermore, the analysis reveals the implicit integration of feminist ideology gender roles within the texts, particularly concerning evolving gender roles in contemporary Korean households. The thematic patterns identified reflect broader social values and ideological transformations embedded in the educational material, conveying underlying messages that promote gender equality and advocate for more equitable social roles. The thematic patterns identified in the texts function not only to organize information but also to foreground specific social actors and actions that align with feminist ideology. By consistently thematizing female subjects, progressive roles, or relational identities, the texts reflect and reinforce broader social values of gender equality and contribute to the ideological transformation toward more equitable gender norms.